2021
DOI: 10.1097/jcma.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Outcome comparison between vaginoscopy and standard hysteroscopy: A retrospective cohort study

Abstract: Background: Hysteroscopy is a traditional diagnostic method, whereas vaginoscopy is a more recent but proven approach. However, most physicians are unfamiliar with vaginoscopy. We aimed to compare the feasibility and tolerability between the two techniques to increase clinical awareness. Methods: We retrospectively reviewed the data of 100 patients who underwent office hysteroscopy with either the standard approach or the vaginoscopic approach between May and July 2019. While the standard hysteroscopy group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…Interleukin-18 (IL-18), high-sensitivity C-reactive protein (hs-CRP), and tumor necrosis factor- α (TNF- α ) are highly sensitive markers of inflammatory factors [ 6 ]. Studies have confirmed that these inflammatory factors can induce and aggravate inflammatory responses, and IL-18 is involved in the occurrence and development of various malignant tumors including gastric cancer through various mechanisms [ 7 ]. After the inflammatory reaction, due to the continuous increase of free radicals and the generation of superoxide, the cells undergo peroxidative damage, resulting in long-term cellular tumors and gastric cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-18 (IL-18), high-sensitivity C-reactive protein (hs-CRP), and tumor necrosis factor- α (TNF- α ) are highly sensitive markers of inflammatory factors [ 6 ]. Studies have confirmed that these inflammatory factors can induce and aggravate inflammatory responses, and IL-18 is involved in the occurrence and development of various malignant tumors including gastric cancer through various mechanisms [ 7 ]. After the inflammatory reaction, due to the continuous increase of free radicals and the generation of superoxide, the cells undergo peroxidative damage, resulting in long-term cellular tumors and gastric cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors have limited the widespread use of hysteroscopy in outpatient clinics [ 6 ]. With the use of vaginoscopy, outpatient hysteroscopy techniques have been further developed and improved [ 7 ]. In this study, the clinical data of patients examined by conventional hysteroscopy and vaginoscopy were analysed and compared to assess the advantages of vaginoscopy in the clinical setting, and the results are reported below.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of complications after hysteroscopy is 1-2.7% ( 9 , 10 , 11 ) . Although some studies have shown that there are fewer surgical complications in vaginoscopy than in standard hysteroscopy ( 7 ) , it has been shown that there is no statistical difference in terms of surgical complications in others ( 12 ) . Serious complications, such as uterine perforation or bleeding are rare in the office setting, but vasovagal reactions occur in 2.3 and 9.0% ( 7 , 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Tien et al. ( 12 ) disinfected the vagina and cervix with betadine-soaked cotton swabs before vaginoscopy and found that there was no significant difference in the genital tract infection rate between the vaginoscopy and standard hysteroscopy groups.…”
Section: Discussionmentioning
confidence: 99%